Treatment options for dialysis access steal syndrome - Papadoulas, Spyros; Kouri, Natasa; Tsimpoukis, Andreas; Kitrou, Panagiotis; Papasotiriou, Marios; Nikolakopoulos, Konstantinos; Verras, Georgios-Ioannis; Panagiotopoulos, Ioannis; Mulita, Francesk; Moulakakis, Konstantinos (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2022)
Vascular access-induced limb ischemia is a known complication of arteriovenous fistulas and grafts. Many techniques have been adopted to prevent steal in high-risk patients and to treat steal in cases of moderate ischemia not controlled with conservative management. A major factor guiding treatment is access flow volume. Management is different when ischemia is combined with the excessive flow in contrast to the combination with normal flow. We describe the most popular techniques encountered in the English literature as a part of a stepwise approach to treating dialysis access steal syndrome. In absence of ischemia, when cardiac issues emerge due to extreme access flow volumes, some of these techniques are also used to decrease flow and protect the heart. Patient’s history, focused clinical examination, color duplex ultrasound examination, pulse oximetry and an angiogram are essential tools to approach this entity.